2000
DOI: 10.1021/jp992736s
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hot Wire Electrochemistry. Coupled Heat and Mass Transport at a Directly and Continuously Heated Wire

Abstract: Microelectrode wires heated directly in situ by an electric current generate mass as well as heat energy transport phenomena. With continuous heating, a stationary surface temperature is established as a result of thermally promoted convection. The geometry of concentration and temperature profiles under these conditions are investigated by cyclic voltammetry, potential step experiments, and finite element simulation of convection and diffusion processes. It is shown that the Nernst diffusion layer approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 16 publications
4
39
1
Order By: Relevance
“…The latter even plays a dominant role. So, there exists a transition of mass transport at the electrode surface from linear diffusion at lower temperature to mixed cylindrical diffusion and convection at high temperature, which is in agreement with our previous work [28].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The latter even plays a dominant role. So, there exists a transition of mass transport at the electrode surface from linear diffusion at lower temperature to mixed cylindrical diffusion and convection at high temperature, which is in agreement with our previous work [28].…”
Section: Resultssupporting
confidence: 92%
“…A single electrode was constructed. A heated electrode consists of two single electrodes and symmetric arrangement [28]. The total geometric area was ca.…”
Section: Construction Of a Heated Gold Wire Electrodementioning
confidence: 99%
“…The two characteristic features associated with the increase of the temperature at the electrode±solution interface in a nonisothermal cell [19] are (i) the increase in current due to the higher diffusivity and faster mass transport and (ii) the shift of the equilibrium potential of the redox system predominantly due to the reaction entropy associated with the redox process [20]. A correction accounting for the Soret effect [21] is assumed to remain insigni®cant. For a solution of 4 mM Fe(CN) 6 4À in aqueous 1 M KCl both the change in diffusivity [22] and the shift of the equilibrium potential, dEydT À1X53 mV K À1 [18], are well known.…”
Section: àmentioning
confidence: 99%
“…A study into the temperature profiles for both the continuous heating and TPV techniques has been reported [32,37,39]. These were modeled at a continuously heated wire using a finite element simulation package (FIDAP, version 8.52 Fluent Europe Ltd., Sheffield, UK, http:// www.fluent.com) [32].…”
Section: Non-isothermal Heating Methods: Ac Heating Of Wiresmentioning
confidence: 99%
“…These were modeled at a continuously heated wire using a finite element simulation package (FIDAP, version 8.52 Fluent Europe Ltd., Sheffield, UK, http:// www.fluent.com) [32]. The results obtained showed that the temperature profile expands into the solution much faster and further than any concentration profile generated electrochemically.…”
Section: Non-isothermal Heating Methods: Ac Heating Of Wiresmentioning
confidence: 99%